Morphological analysis of air sacs in red-winged tinamou (Rhynchotus rufescens Temminck, 1815) - Viegas, Katia Aparecida da Silva (2024)
Anatomical descriptions of partridges’ air sacs of the species Rhynchotus rufescens are scarce.This study aimed to evaluate the air sacs of this species. Ten cadaveric specimens of adult partridges,approximately 1 year old, were collected, and latex perfusion was used to solidify the material. Thecervical air sac of a red-winged tinamou is smaller and has a more irregular conformation than other airsacs. The thoracic air sacs are symmetrical, and the cranial thoracic air sacs are smaller than the caudalones. The abdominal air sacs are asymmetrical, and the largest ones extend themselves to the cloaca.Only one clavicular air sac was found, with three subdivisions: right, left, and medial. Additionally, rightand left extrathoracic portions were found, passing under the clavicle. In one of the animals, the latexfilledhumeri were found, and in three other ribs, vertebral diverticula were present. There is no clearrelationship between taxonomy and biology versus the quantity and conformation of air sacs, becausedifferent animals with taxonomic proximity present differences. This study enhances species-specificanatomical knowledge of this species of partridge.